Turkish Gastroenterology Association, Pancreas Study Group, Chronic Pancreatitis Committee Consensus Report - Soytürk, Müjde; Bengi, Göksel; Oğuz, Dilek; Kalkan, İsmail Hakkı; Yalnız, Mehmet; Tahtacı, Mustafa; Demir, Kadir; Kasap, Elmas; Oruç, Nevin; Ünal, Nalan Gülşen; Sezgin, Orhan; Özdoğan, Osman; et al. (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Soytürk M, Bengi G, Oğuz D, et al. Turkish Gastroenterology Association Pancreas Study Group Chronic Pancreatitis Committee Consensus Report. Turk J Gastroenterol 2020; 31(Suppl 1) S1-41.